Princess in the spotlight - Cabot, Meg. (New York : HarperCollins, 2001)
Having recently discovered she is the sole heir to the throne of a tiny European principality, fourteen-year-old Manhattan resident Mia writes in her journal about her attempts to cope with this news, as well as with more typical teenage concerns.
850
Accelerated Reader AR
Keywords: Princesses -- Juvenile fiction; Diaries -- Juvenile fiction; Schools -- Juvenile fiction; Identity -- Juvenile fiction; New York (N.Y.) -- Juvenile fiction